2013
DOI: 10.1371/journal.pmed.1001505
|View full text |Cite
|
Sign up to set email alerts
|

First Diagnosis and Management of Incontinence in Older People with and without Dementia in Primary Care: A Cohort Study Using The Health Improvement Network Primary Care Database

Abstract: Robert Grant and colleagues used the British THIN primary care database to determine rates of first diagnosis of urinary and faecal incontinence among people aged 60–89 with dementia compared with those without dementia, and the use of medication or indwelling catheters for urinary incontinence in those with and without dementia. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 32 publications
(30 reference statements)
1
54
0
1
Order By: Relevance
“…In a UK General Practitioner database, when compared with those without a dementia diagnosis, dementia was associated with approximately three times the rate of diagnosis of UI. The incidence rates of first diagnosis per 1000 person-years at risk for UI in the dementia cohort, among men and women, respectively, were 42.3 [95 % confidence interval (CI) 40.9-43.8] and 33.5 (95 % CI 32.6-34.5) [24]. When assessed urodynamically, the majority of incontinence associated with dementia appears to be related to detrusor overactivity, resulting in urgency incontinence [25,26].…”
Section: Dementia and Incontinencementioning
confidence: 99%
“…In a UK General Practitioner database, when compared with those without a dementia diagnosis, dementia was associated with approximately three times the rate of diagnosis of UI. The incidence rates of first diagnosis per 1000 person-years at risk for UI in the dementia cohort, among men and women, respectively, were 42.3 [95 % confidence interval (CI) 40.9-43.8] and 33.5 (95 % CI 32.6-34.5) [24]. When assessed urodynamically, the majority of incontinence associated with dementia appears to be related to detrusor overactivity, resulting in urgency incontinence [25,26].…”
Section: Dementia and Incontinencementioning
confidence: 99%
“…Faecal incontinence is likely to be more prevalent among CH residents living with dementia than in the general population. In a study of primary care patients, the rate of FI diagnosis was four times higher for people with dementia than in a matched group without a diagnosis of dementia, (Grant et al 2013) but these figures don't differentiate between FI and toileting difficulties. However, FI alone is relatively uncommon.…”
Section: Box 2 -Issues To Consider or Address For People Living With mentioning
confidence: 97%
“…The focus on avoiding or treating constipation may be exacerbating FI, and careful thought 13,14 Epidemiological studies have identified dementia as an independent risk factor for FI, [15][16][17] and a study of primary care patients found FI to be four times higher in people with dementia than in a matched community-dwelling sample with FI but without a diagnosis of dementia. 18 Studies suggest that the prevalence of FI in care homes is between 30% and 50%. 15,[19][20][21][22][23] The level of variation is believed to reflect differences in care and the way in which continence is defined (by frequency, amount and detection method) as well as the individual characteristics of older people.…”
Section: Conclusion and Implications For Health Carementioning
confidence: 99%